A study of socio-economic and motivational factors related to intelligence and achievement of G.C.E. (O.L) students in certain selected schools in the Jaffna district. - Walton, C.R.P. (My University, 1980)
It is vitally important that all children should have equal opportunity to realise their potential abilities to the full. Discrepancies in school achievement have been accounted for by differences in innate ability, by the variation in socio-economic factors of the home environment of students and in more recent years by personality differences among them...